Bibliometric Insights into Mental Health Challenges and Innovations in Contemporary Society - Judijanto, Loso; Lesmana, Tera (The Eastasouth Journal of Social Science and Humanities, 2024)
This bibliometric analysis examines the evolution and current state of mental health research from a comprehensive, data-driven perspective. Using VOSviewer for visual mapping, this study highlights key terms, thematic developments, and influential authors within the field over several decades. The analysis reveals a strong ongoing focus on core issues such as "mental illness," "anxiety," and "depression," alongside a notable rise in the integration of technological innovations like telepsychiatry and mobile health applications. The study also identifies significant authorship networks that suggest robust collaborative efforts, which are crucial for advancing research and implementing effective mental health interventions. The findings point towards an increasing recognition of the impact of social and environmental factors on mental health, suggesting new directions for future research and policy-making. This study underscores the need for a dynamic approach to mental health research, one that adapts to emerging challenges and leverages technological advances to improve access to care and treatment outcomes.